Adequate nutrient levels and plant density for the rice experiments under greenhouse conditions - Fageria, Nand Kumar; Barbosa Filho, Morel Pereira; Garber, Morris Joseph (Pesquisa Agropecuaria Brasileira, 2014)
Two greenhouse pot experiments were conducted with rice (Oryza sativa L.) – cultivar IAC 47 and IR 841-3-6-3) - to evaluate different nutrient levels and plant densities. The nutrient levels were zero, normal levels recommended under field conditions, and four and eight times the normal levels. These levels were tested at four plant densities, i.e., one, two, three and four plants per pot. Regression analysis indicated that yield and the yield components were affected by nutrient level, density, and in most cases by the interaction between these two factors. In both cultivars, potassium was absorbed in greater quantities and phosphorus in less quantities in comparison to the other nutrients. The results showed that adequate nutrient levels for upland and irrigated rice cultivated in 6 kg pots were aproximately eight times those recommended for field conditions. Optimum plant density was obtained with 2 to 3 plants per pot.
Keywords: Oryza sativa; cultivars; field conditions